Modul Matematika Berdasarkan Model Pembelajaran Problem Based Learning Materi Pokok Trigonometri - Angraini, Nia; Masykur, Rubhan (Desimal: Jurnal Matematika, 2018)
The purpose of this study is to develop a mathematic module based on Problem Based Learning method trigonometry lessons for Senior High School. In this study use R&D (Research and Development) Borg and Gall modified from sugiyono, the procedure used as follows: (1) potential and problems, (2) data collection, (3) product design, (4) product validation, (5) product revision, (6) product trial, (7) product revision. Data collection techniques used areinterview, kuisioner, observation, and document. Validaton is done by material experts, media experts, and linguists. Trials are conducted through two stages is small group trials and field trials. Validation results material experts, media experts, and linguists obtained the average value with valid criteria. On field trials determine the response of learners in Senior High School Muhammadiyah 2 Bandar Lampung, in Senior High School AL-AZHAR 3, and in Senior High School Muhammadiyah 2 Bandar Lampung obtained average value of 3,58 with criteria very interesting.